Retail SMEs' performance under impacts of technological uncertainty - Van Hoang Dinh; Thi Hien Nguyen; Kieu Minh Thi Tran; Anh Tuan Doan (Innovation & Management Review, 2025)
The study aims to clarify the impact of technological uncertainty (TU) on emerging market retail SMEs' performance with the mediating roles of digital capabilities (DCs) and marketing innovation capability (MarIC).The research applied a convenience sampling including 271 valid responses collected from Vietnamese small and medium-sized enterprises (SMEs) in the retail industry. The paper employed partial least squares-structural equation modeling as an analysis technique.The findings show that TU has a positive significant statistical impact on retail SMEs' performance. Furthermore, DCs and MarIC serve as mediators in the relationship between TU and firm performance.This research emphasizes both theoretical and practical contributions, especially practical implications for emerging market retail SMEs in enhancing DCs and innovation capability in marketing to facilitate firms to adapt to TU.
https://www.emerald.com/inmr/article-supplement/1311790/docx/inmr-10-2023-0172_suppl1/
Keywords: 650; Digital capabilities; Firm performance; Marketing innovation capability; Technological uncertainty